Electrosprayed maize starch and its constituents (amylose and amylopectin) nanoparticles. (23rd March 2015) - Ghaeb, Maryam; Tavanai, Hossein; Kadivar, Mehdi
<x xml:space="preserve">Abstract</x> Starch consists of amylose and amylopectin. Properties such as being natural and highly hygroscopic as well as biodegradability have opened a considerable range of applications for amylose, amylopectin and starch. The performance of particles is highly dependent on their size which in turn determines the specific surface area. This work studies the application of electrospraying to fabricate maize starch and its constituents: amylose and amylopectin nanoparticles. This study showed that electrospraying technique is capable of producing amylose, amylopectin and starch nanopowder with an average particle size around 100 nm. FTIR analysis showed no reaction or interaction occurring in amylose, amylopectin and starch nanoparticle compared with their natural form. Basically, lower concentration, lower viscosity and lower surface tension of the electrospraying solution as well as higher nozzle–collector distance, higher voltage and lower feed rate lead to smaller nanoparticle size. Copyright © 2015 John Wiley & Sons, Ltd.